Hubungan Tingkat Pengetahuan Remaja dengan Perilaku Hidup Bersih dan Sehat di SMA Patriot Kota Bekasi - Febiyanti, Murtian Clara Adelia; Rizana, Anna (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Clean and healthy living behavior is a step that must be taken to achieve optimal health for each individual, especially for groups of adolescents, it is very important to be made aware of the importance of maintaining their health, this aims so that adolescents can adopt healthy living behaviors. To have a healthy condition is not easy, but efforts must be made to live a healthier life and create a comfortable environment. This effort must start from instilling a healthy mindset in adolescents which must be initiated and cultivated by themselves. This effort is made to realize the highest public health as a capital for the quality of productive human resources. Striving for this behavior requires a joint commitment to support each other in improving the health of adolescents, especially families so that health development can be achieved optimally. To analyze the relationship between the level of knowledge of adolescents with clean and healthy living behavior. The type of research method used in this research is quantitative research and with a cross-sectional approach, which is a form of observational (non-experimental) study. The technique used is probability sampling by means of random sampling. From 151 respondents, the chi square test value showed that there was a relationship between the knowledge level of adolescents and clean and healthy living behavior at Patriot High School, Bekasi City, with a P-value of 0.011 (p <0.05), so Ha was accepted and Ho was rejected. There is a relationship between the level of knowledge of adolescents with clean and healthy living behavior at Patriot High School, Bekasi City. It is hoped that it can be additional information as an effort to increase knowledge and healthy living behavior so that in the next life it has good PHBS quality. Keywords: Knowledge, Clean and Healthy Living Behavior.  ABSTRAK Perilaku hidup bersih dan sehat merupakan langkah yang harus dilakukan untuk mencapai kesehatan yang optimal bagi setiap individu, khususnya kelompok remaja sangat penting untuk disadarkan akan pentingnya menjaga kesehatannya, hal ini bertujuan agar remaja dapat menerapkan perilaku hidup yang sehat. Untuk memiliki kondisi yang sehat itu tidak mudah, tetapi harus diupayakan untuk hidup yang lebih sehat serta menciptakan lingkungan yang nyaman. Upaya ini harus dimulai dari menanamkan pola pikir sehat pada remaja yang harus dimulai dan diusahakan oleh diri sendiri. Upaya ini dilakukan untuk mewujudkan kesehatan masyarakat setinggi-tingginya sebagai satu modal bagi kualitas sumber daya manusia yang produktif. Dalam mengupayakan perilaku ini dibutuhkan komitmen bersama-sama saling mendukung dalam meningkatkan kesehatan remaja khususnya keluarga sehingga pembangunan kesehatan dapat tercapai secara optimal. Menganalisis hubungan tingkat pengetahuan remaja dengan perilaku hidup bersih dan sehat. Jenis metode penelitian digunakan dalam penelitian ini adalah penelitian kuantitatif serta dengan pendekatan cross sectional yaitu merupakan bentuk studi observasional (non eksperimental). Teknik yang digunakan adalah probability sampling dengan cara random sampling. Dari 151 responden di dapatkan nilai uji chi square menunjukkan adanya hubungan tingkat pengetahuan remaja dengan perilaku hidup bersih dan sehat di SMA Patriot Kota Bekasi dengan P-value 0,011 (p<0,05) maka Ha diterima dan Ho ditolak. Adanya hubungan tingkat pengetahuan remaja dengan perilaku hidup bersih dan sehat di SMA Patriot Kota Bekasi. Diharapkan dapat menjadi tambahan informasi sebagai upaya meningkatkan pengetahuan dan perilaku hidup bersih sehat agar dikehidupan selanjutnya memiliki kualitas  PHBS yang baik. Kata Kunci : Pengetahuan, Perilaku Hidup Bersih Dan Sehat.